Origins and implications of the Caribbean Basin Initiative : mortgaging sovereignty? - Polanyi-Levitt, Kari (1985)
Traces the origins and discusses the implications of the Caribbean Basin Initiative since it was first proposed by Edward Seaga in October 1979.